Every minute on Earth : fun facts that happen every 60 seconds - Murrie, Steve; Murrie, Matthew; Lloyd, Mary Anne (New York : Scholastic Reference, 2007)
Contains over two hundred facts and figures about occurrences around the world which take place in a minute.
Includes index.
5.9
3-6
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Curiosities and wonders